Effect of Zinnia peruviana root extract on the production of microbial biofilms - Mohamed, Ana Mariel (2021)
The increase of antimicrobial resistance is a growing global public health. One mechanism by which microorganisms acquire resistance to antibiotics is the biofilms. Approximately 80% of chronic and recurrent microbial infections are due to this resistance strategy produced by a diverse group of microorganisms. This context has motivated the search for new antimicrobial substances with anti-biofilm activity. The extensive and varied flora of the Central West Region of Argentina offers an important resource for the study of natural products in the search for antimicrobials with potential therapeutic use in clinical infections. Within these species, Zinnia peruviana (L.), is an herb with proven antimicrobial properties in its aerial part. The objective of this work was to evaluate the effect of the addition of acetonic extract from the roots of Z. peruviana at different concentrations on the biofilm production of L. monocytogenes, E. coli and C. albicans. Biofilm production was evaluated by determining adherence to 96-well microplates U-bottom. The tested extract inhibited 29% and 50% of the biofilm production of L. monocytogenes with 0.625 mg ml-1 and 5 mg ml-1 respectively. For E. coli the reduction was 33% (0.625 mg ml1 ) and 51% (0.078 mg ml-1) while for C. albicans a significant reduction in biofilm formation was observed with 3 concentrations of extract: 59% (5 mg ml-1), 42% (0.625 mg ml-1) and 44% (0.078 mg ml-1). All the biofilm reduction values showed significant differences (p<0.05). The high biological activity of the roots of Z. peruviana represents an alternative potential for the treatment and control of microbial infections. Further studies on toxicity and bioapplicability are needed.